The Participation of Worthy Age in the Use of Contraceptive Equipment during the Covid-19 Pandemic in the Working Area of Batuyang Public Health Center, Pringgabaya District, East Lombok - Dwi Andayani; Ni Komang Wijani Yanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The use of contraceptives fell by 47 percent in Indonesia during the Covid-19 pandemic and a decline in family planning services by 1,179,467 family planning services during January-April 2020. These conditions can increase the number of unplanned pregnancies resulting in a population explosion. In East Lombok district, it is known that the highest birth and infant mortality rates are in the working area of BatuYang Health Center, Pringgabaya District, with 1264 people, namely 1246 births and 18 infant deaths. Where out of 9512 PUS in Pringgabaya sub-district, only 92.3 percent are already using contraceptives. The research method uses a cross sectional study approach with quantitative and qualitative approaches. Statistical tests to determine the existence of a relationship use the chi square test, to determine the most influential variable using multiple logistic regression, while for the qualitative approach the data collection technique is through FGD. The results of the chi-square test can be seen that the level of education (p-value = 0.021) and access to family planning services (p-value = 0.028) are significantly related to the participation of couples of childbearing age in using family planning contraceptives during the COVID-19 pandemic in the Work Area. BatuYang Health Center, Pringgabaya District, East Lombok Regency. Meanwhile, the variables of age, knowledge, and husband's support were not significantly related to the participation of couples of childbearing age in the use of contraceptives during the COVID-19 pandemic. The results of the analysis using multiple logistic regression tests, the most significant variable on the participation of couples of childbearing age in the use of family planning contraceptives during the COVID-19 pandemic was Education (p-Value = 0.019).